Validity and psychometric properties of Malay translated religious orientation scale-revised among Malaysian adult samples - Mohammad Rahim Kamaluddin,; Rohany Nasir,; Wan Shahrazad Wan Sulaiman,; Rozainee Khairudin,; Zainah Ahmad Zamani, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Religious Orientation Scale-Revised (ROS-R) has been used increasingly as an important measure in psychology of religion based researches and widely administered in cross-cultural settings. Unfortunately, there is no valid and reliable ROS-R available in Malay language to assess religious orientations among Malaysians. With that in mind, the present study aims to validate and document the psychometric properties of Malay translated ROS-R (henceforth, M-ROS-R) among sample of Malaysian adults. This study commenced with Forward-Backward translations and was followed by content and face validities. Subsequently, a cross-sectional study was conducted among Malaysian adults (n = 226) using convenience sampling method for the purpose of construct and factorial validations. Later, construct and factorial validity was performed via Exploratory Factor Analysis using Principal Component Analysis with Varimax rotation. Finally, reliability testing was performed to determine the internal consistency of the items which was achieved using Cronbach’s Alpha coefficient method (α). The factor loading consisted of three factors with a total variance of 64.76%. The final version of M-ROS-R consisted of 14 items with Factor 1 (Intrinsic Orientation) comprised of 8 items, Factor 2 (Extrinsic-Socially Orientated) with 3 items while Factor 3 (Extrinsic-Personally Orientated) constituted 3 items. The internal consistency values of the factors ranged between 0.68 and 0.86, indicating the scale is reliable. The intercorrelations between factors were also significant with each other. M-ROS-R was concluded as a valid and reliable scale to measure and assess religious orientations among Malaysians.